2020
DOI: 10.1167/tvst.9.11.27
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of Suprachoroidal Injection Procedure Utilizing a Microinjector across Three Retinal Disorders

Abstract: Purpose This study assessed physician-investigator experience with suprachoroidal (SC) injections, an investigational therapeutic administration technique using a 900 or 1100 µm microneedle to inject drugs into the SC space. Methods Datasets from six clinical trials across three diseases (noninfectious uveitis; diabetic macula edema, and retinal vein occlusion) were assessed. In addition to a user survey, retrospective correlations were performed between procedural vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Further analysis revealed moderate correlations between the site of injection and the ultimate needle length used to deliver study drug, with the 900 µm needle being most commonly used in the superotemporal quadrant and the 1100 µm needle being most frequently used in the inferonasal quadrant [56]. This aligns with known scleral thickness variations, with the superotemporal quadrant generally showing the thinnest scleral of the quadrants [19,22].…”
Section: Effect Of Microneedle Length On Suprachoroidal Injectionmentioning
confidence: 75%
See 1 more Smart Citation
“…Further analysis revealed moderate correlations between the site of injection and the ultimate needle length used to deliver study drug, with the 900 µm needle being most commonly used in the superotemporal quadrant and the 1100 µm needle being most frequently used in the inferonasal quadrant [56]. This aligns with known scleral thickness variations, with the superotemporal quadrant generally showing the thinnest scleral of the quadrants [19,22].…”
Section: Effect Of Microneedle Length On Suprachoroidal Injectionmentioning
confidence: 75%
“…A post hoc analysis was conducted across six clinical trials (PEACHTREE, AZALEA, TANZANITE, TOPAZ, SAPPHIRE, and TYBEE) focusing on baseline injections, the first suprachoroidal injection administered by the investigator to a patient. In this analysis, the 900 µm needle was used for 71% (412 of 581) of suprachoroidal injections; the 1100 µm needle was subsequently used to complete the remaining injections [55,56]. Additionally, in response to the prompt 'Was the suprachoroidal injection administered?…”
Section: Effect Of Microneedle Length On Suprachoroidal Injectionmentioning
confidence: 99%
“…Delivery to the SCS via microneedles exhibit convenient pharmacodynamics preclinically as it provides posterior and circumferential distribution of agents injected anteriorly (20,23) and it has been shown to be safe and effective clinically in Phase 3 trials of CLS-TA using microneedle-based technology, the SCS Microinjector® (Clearside Biomedical, Alpharetta, GA), which is supplied with two 30G microneedles with xed free lengths of 900 or 1100 μm (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of therapeutics into the SCS provides a novel alternative approach that has theoretical appeal, as it dominantly targets chorio-retinal tissues with posterior and circumferential distribution while relatively restraining delivery to the unaffected anterior segment and the vitreous chamber, thus reducing hazards associated with off-target effects which enhances its safety pro le (20). This hypothesis was further proven by many preclinical and clinical studies through microinjectors (21)(22)(23)(24)(25), which has been shown to provide a safe, minimally invasive, and reliable method of targeting SCS (25). In addition, extended duration of action and desirable pharmacokinetic properties have been reported for small molecule suspensions including Triamcinolone Acetonide (TA), with the potential to lessen the burden of treatment (21).…”
Section: Introductionmentioning
confidence: 99%
“… 29 A recent study assessed physician–investigator experience with microneedle-based SC injection across six clinical trials and three disease states. 30 A user survey was conducted, along with a retrospective correlation analysis between procedural variables, demographics, and ocular characteristics. This study demonstrated that microneedle-based SC injection is well accepted by physician–investigators, and that it can accommodate a wide range of anatomic and demographic variables.…”
Section: Introductionmentioning
confidence: 99%